Marriage Law For A Girl Produced of Adultery and Her Biological Father According to Four Mazhabs Based on Hifdzunnasl (Comparative Study of Istinbatul Ahkam Madzahibul Arba'ah)" - Jamarudin, Ade; Abdul Mufti Albasyari; M. Maisan Abdul Ghani; Hamidah; Imam Sucipto (al-Afkar, Journal For Islamic Studies, 2024)
The phenomenon of marrying a daughter resulting from adultery is taboo in society. In this case, Islamic scholars from four schools of thought have different opinions regarding the legal determination of the marriage between a daughter resulting from adultery and her biological father. The problematic outcome of the offspring from this marriage must be considered with maqosyidussyari'ah using the concept of hifdzunnasl. The aim of this research is to: Find out the relevance of the opinions of the Four Schools regarding the law of marriage between girls resulting from adultery and their biological fathers in relation to Islamic law in Indonesia and determine the impact of inbreeding between girls resulting from adultery and their biological fathers. The research method used is qualitative, with a library research approach, and a descriptive- analytic type of research. Research results: The marriage of a daughter resulting from adultery and her biological father according to the Hanafiyah and Hanabilah schools of thought is haram, whereas according to the Malikiyah and Syafi'iyah schools of thought it is halal but makruh. Provisions in Indonesian positive law tend to prohibit the issue of children marrying their biological father, especially with the presence of the Constitutional Court decision Number 46/PUU-VIII/2010.